2007
DOI: 10.1007/s11199-007-9348-4
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Gender Development: Associations with Parental Sexual Orientation, Attitudes, and Division of Labor

Abstract: Research on children of lesbian parents has suggested that such children are developing well, but questions have been raised about their gender development. In this study, we explored associations among parental sexual orientation, parental gender-related attitudes, parental division of labor, and children's gender development. Participants were 66 preschool children and their 132 parents from the East Coast of the United States. Thirty-three families were headed by lesbian and 33 by heterosexual couples. Pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
3
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(131 citation statements)
references
References 39 publications
(45 reference statements)
6
112
3
8
Order By: Relevance
“…In addition, in homosexual couples, in which gender divisions are not established beforehand, the idea of egalitarian division is prevalent. The interviewed women's reports corroborate some studies which point out the existence of egalitarianism among women in lesbian couples in regards to sharing maternal care tasks (Fulcher, Sutfin, & Patterson, 2008;Patterson, Sutfin & Fulcher, 2004).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In addition, in homosexual couples, in which gender divisions are not established beforehand, the idea of egalitarian division is prevalent. The interviewed women's reports corroborate some studies which point out the existence of egalitarianism among women in lesbian couples in regards to sharing maternal care tasks (Fulcher, Sutfin, & Patterson, 2008;Patterson, Sutfin & Fulcher, 2004).…”
supporting
confidence: 80%
“…Some studies conducted with children of homosexuals have been concerned with four types of questions for decades: sexual identity, personal development, their social relationships with peers and adults; and the risk of sexual abuse (Fulcher, Sutfin, & Patterson, 2008;Golombock et al, 2003;MacCallum & Golombock, 2004). Such studies showed that there are no significant differences in regards to the four main topics studied between children raised in heterosexual households and those raised by same-sex parents (Gross, 2013) The studies mentioned and their public dissemination were and are greatly important.…”
Section: Families Homosexualities and Homoparentalitiesmentioning
confidence: 99%
“…It is important to remember that although these plans may be sharpened in college, students have been surrounded by idealized images of the breadwinner-caregiver model throughout childhood (Ex et al 2002;Smith et al 2010). Additionally, they have created templates for their future roles by observing their parents, who typically also divided labor in a gendered way (Fulcher et al 2008). Thus, the breadwinner-caregiver model may be the only model they have considered, which may make it difficult to break free of those gender restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing children raised by lesbian or gay parents with children raised by heterosexual parents have discovered no significant differences in terms of children's social and emotional adjustment, gender role identification, or sexual orientation (in Northern Europe: Golombok et al 1983;Golombok and Tasker 1996;in North America: Farr et al 2010;Fulcher et al 2008). Research therefore shows that deviation from the traditional nuclear family structure does not constitute an obstacle per se to the creation of a healthy family environment.…”
Section: Introductionmentioning
confidence: 99%